2013
DOI: 10.1016/j.diii.2012.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of haemoptysis: Medium and long-term assessment

Abstract: BAE is an effective treatment. Aspergilloma is a major risk factor in the recurrence of haemoptysis. Repeated embolisation may be proposed for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
13

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 24 publications
1
21
1
13
Order By: Relevance
“…However, increasingly it is used in moderate hemoptysis and recurrent mild hemoptysis that hampers the lifestyle of the patient. 9,10,16,17 The majority of our patients (58.4%) had moderate hemoptysis. Recurrent mild hemoptysis was present in 21% of patients and the rest had severe hemoptysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, increasingly it is used in moderate hemoptysis and recurrent mild hemoptysis that hampers the lifestyle of the patient. 9,10,16,17 The majority of our patients (58.4%) had moderate hemoptysis. Recurrent mild hemoptysis was present in 21% of patients and the rest had severe hemoptysis.…”
Section: Discussionmentioning
confidence: 99%
“…This can be attributed to the increasing use of microcatheters as has been mentioned in recent studies. [8][9][10][11][12][13] With microcatheters, it is now possible to safely deliver the embolization material beyond the origin of the spinal arteries thus preventing this complication. We encountered only minor complications such as non-progressive localized dissection and chest pain.…”
Section: 1118mentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, a study by Racil et al reported the short (< 30 days) and medium-term (> 30 days and < 3 years) recurrence rate of haemoptysis was 17.39% and 8.69% respectively after BAE in 53 consecutive patients. 15 The 50% episodes of short-term recurrences were related to aspergilloma and 80% of the patients with aspergilloma had short-term recurrence. The long-term recurrence (>3 years) of haemoptysis was also related to aspergilloma.…”
Section: First Performed In 1973 Bymentioning
confidence: 99%